Developing English Materials for Efl Learners at Islamic Junior High School - Syafi’i, Muhammad Lukman; Gestanti, Rohfin Andria (JEELS (Journal of English Education and Linguistics Studies), 2017)
The purpose of this research was to develop an EFL course book for the first semester learners at the Islamic junior high school in Indonesia. The material development includes some procedures of need analysis, material development, expert validation, material revision, try-out and final revision. Based on the results of questionnaires distributed to 106-second graders, the interviews done to the teachers and field notes taken from a document of the syllabus, this research revealed that most of the students and English teachers require English instructional materials embracing religious and general knowledge. After validated by the experts and tried-out to the students, this research finally produced English materials that were supplemented by a teacher‟s guide, student‟s worksheets and a CD containing listening materials.